The characteristics of acoustic propagation and unfrozen water in silt under freezing-thawing conditions - Jia, Sheng-Ao; Fan, Qi; Pang, Wei-Xin; Fu, Qiang; Chen, Pan (Frontiers in Materials, 2025)
This study employs nuclear magnetic resonance and acoustic testing methods to investigate the evolutions in unfrozen water content and shear wave velocity of silty soils, both with and without chloride salt contamination, under freeze–thaw cycles. The effects of saline solution and freezing–thawing processes on the soil-water state and acoustic properties were systematically assessed. The results indicate that the addition of sodium chloride lowers the soil freezing temperature from roughly −1.6 °C to −4 °C, causing an undercooling depression of approximately 2.4 °C. This causes a significant delay in the phase transition of pore water. In the case of salt-free silty soil, the unfrozen water content dramatically decreases from 27.2% to 1.7% at the freezing point, exhibiting pronounced hysteresis during the thawing processes. On the other hand, the reduction of unfrozen water content in chloride salt–contaminated soil is more gradual, resulting in less pronounced hysteresis effects. Freezing-thawing cycles induce a reorganization of the pore structure, evidenced by a reduced micropore fraction and an increased macropore fraction. These alterations are more pronounced in salt-free soils. The shear wave velocity increases as the temperature drops during freezing and rises during thawing. Notably, the wave velocity reaches approximately 2,220 m/s for salt-free soil and 1944 m/s for salt-contaminated soil at −10 °C. When subjected to identical temperature conditions, the shear wave velocities in salt-contaminated soils are 200–300 m/s lower than those in salt-free soils. Variations in frequency between 10 and 30 kHz yield a difference of less than 3%. These findings provide valuable insights for understanding the freeze-thaw mechanisms in saline soils and hold significant implications for geotechnical engineering in cold regions.